Lazy Multi-label Learning Algorithms Based on Mutuality Strategies - Cherman, Everton Alvares; Spolaôr, Newton; Valverde-Rebaza, Jorge; Monard, Maria Carolina (Journal of intelligent & robotic systems, 2015)
Lazy multi-label learning algorithms have become an important research topic within the multi-label community. These algorithms usually consider the set of standard k -Nearest Neighbors of a new instance to predict its labels (multi-label). The prediction is made by following a voting criteria within the multi-labels of the set of k -Nearest Neighbors of the new instance. This work proposes the use of two alternative strategies to identify the set of these examples: the Mutual and Not Mutual Nearest Neighbors rules, which have already been used by lazy single-learning algorithms. In this work, we use these strategies to extend the lazy multi-label algorithm BRkNN . An experimental evaluation carried out to compare both mutuality strategies with the original BRkNN algorithm and the well-known MLkNN lazy algorithm on 15 benchmark datasets showed that MLkNN presented the best predictive performance for the Hamming-Loss evaluation measure, although it was significantly outperformed by the mutuality strategies when F-Measure is considered. The best results of the lazy algorithms were also compared with the results obtained by the Binary Relevance approach using three different base learning algorithms.